The downfall of Turkish–Israeli relations: a cold peace between former strategic allies. Issue 5 (2nd September 2020) - Uzer, Umut
ABSTRACT: The entire edifice of the strategic Turkish-Israeli alliance of the 1990s collapsed during the last ten years, with relations between the former partners characterised by antagonism and total lack of trust that make a genuine reconciliation rather inconceivable despite the existence of weighty common military and economic interests. This article examines the origins of the bilateral relations, the main causes of its decline, and the prospects for a future thaw.